TET family regulates the embryonic pluripotency of porcine preimplantation embryos by maintaining the DNA methylation level of NANOG - Kyungjun Uh; Junghyun Ryu; Kayla Farrell; Noah Wax; Kiho Lee (Epigenetics, 2020)
The ten-eleven translocation (TET) family (TET1/2/3) initiates conversion of 5-methylcytosine to 5-hydroxymethylcytosine, thereby orchestrating the DNA demethylation process and changes in epigenetic marks during early embryogenesis. In this study, CRISPR/Cas9 technology and a TET-specific inhibitor were applied to elucidate the role of TET family in regulating pluripotency in preimplantation embryos using porcine embryos as a model. Disruption of TET1 unexpectedly resulted in the upregulation of NANOG and ESRRB transcripts, although there was no change to the level of DNA methylation in the promoter of NANOG. Surprisingly, a threefold increase in the transcript level of TET3 was observed in blastocysts carrying modified TET1, which may explain the upregulation of NANOG and ESRRB. When the activity of TET enzymes was inhibited by dimethyloxalylglycine (DMOG) treatment, a dioxygenase inhibitor, to investigate the role of TET1 while eliminating the potential compensatory activation of TET3, reduced level of pluripotency genes including NANOG and ESRRB, and increased level of DNA methylation in the NANOG promoter was detected. Blastocysts treated with DMOG also presented a lower inner cell mass/TE ratio, implying the involvement of TET family in lineage specification in blastocysts. Our results indicate that the TET family modulates proper expression of NANOG, a key pluripotency marker, by controlling its DNA methylation profile in the promoter during embryogenesis. This study suggests that TET family is a critical component in pluripotency network of porcine embryos by regulating gene expression involved in pluripotency and early lineage specification.